2021
DOI: 10.1111/sjpe.12278
|View full text |Cite
|
Sign up to set email alerts
|

Public and private pension systems and macroeconomic volatility in OECD countries

Abstract: This paper analyses the impact of public pension expenditures and pension funds' assets as well as their benefits on economic volatility. To do so, we use panel data for 35 OECD countries for the period 1980-2018 and apply a set of state-of-the-art econometric estimators. Our results show weak evidence of a negative impact of public pension expenditures as well as weak evidence of a positive impact of pension funds' benefits on volatility. Results were, however, found not to be very robust. In contrast, pensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…it is constantly growing. These findings confirm and develop the existing scientific views on the relationship between pension savings and economic growth (Altiparmakov & Nedelkovic, 2018;Apilado, 1972;Bijlsma et al, 2018;Davis & Hu, 2008;Holzner et al, 2021;Iparraguirre, 2020;Keller, 2018;Zandberg & Spierdijk, 2013) while providing an alternative expression of the type of such dependence compared to studies by Holzmann (1997), Davis and Hu (2008), and Hu (2005).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…it is constantly growing. These findings confirm and develop the existing scientific views on the relationship between pension savings and economic growth (Altiparmakov & Nedelkovic, 2018;Apilado, 1972;Bijlsma et al, 2018;Davis & Hu, 2008;Holzner et al, 2021;Iparraguirre, 2020;Keller, 2018;Zandberg & Spierdijk, 2013) while providing an alternative expression of the type of such dependence compared to studies by Holzmann (1997), Davis and Hu (2008), and Hu (2005).…”
Section: Discussionsupporting
confidence: 88%
“…For a long time, scientific studies on the impact of pension fund assets on macroeconomic indicators have shown an increase in economic growth due to an increase in the aggregate level of savings shaped in pension assets available for investment (Altiparmakov & Nedelkovic, 2018;Apilado, 1972;Bijlsma et al, 2018;Davis & Hu, 2008;Holzner et al, 2021;Iparraguirre, 2020;Keller, 2018;Zandberg & Spierdijk, 2013). In addition, Bayar (2017) denotes a two-way causal link between pension fund assets and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[36], through building an economic model, shows that population life expectancy growth will increase pension fund spending. As an important source of economic development, pension fund assets are important for long-term investment in less developed countries [37]. Increased pension spending inevitably reduces the amount of pension retained, but pension spending can boost economic growth by stimulating consumption.…”
Section: Population Aging Endowment Insurance Expenditure and Economi...mentioning
confidence: 99%